Interaction of D-amino acid oxidase with carbon nanotubes: Implications in the design of biosensors - Mora, Maria F. (2009)
We have investigated the interaction of D-amino acid oxidase (DAAO) with single-walled carbon nanotubes (CNT) by spectroscopic ellipsometry. Dynamic adsorption experiments were performed at different experimental conditions. In addition, the activity of the enzyme adsorbed at different conditions was studied. Our results indicate that DAAO can be adsorbed to CNT at different pH values and concentrations by a combination of hydrophobic and electrostatic interactions. Considering that the highest enzymatic activity was obtained by adsorbing the protein at pH 5.7 and 0.1 mg·mL-1, our results indicate that DAAO can adopt multiple orientations on the surface, which are ultimately responsible for significant differences in catalytic activity. that DAAO can adopt multiple orientations on the surface, which are ultimately responsible for significant differences in catalytic activity. oxidase (DAAO) with single-walled carbon nanotubes (CNT) by spectroscopic ellipsometry. Dynamic adsorption experiments were performed at different experimental conditions. In addition, the activity of the enzyme adsorbed at different conditions was studied. Our results indicate that DAAO can be adsorbed to CNT at different pH values and concentrations by a combination of hydrophobic and electrostatic interactions. Considering that the highest enzymatic activity was obtained by adsorbing the protein at pH 5.7 and 0.1 mg·mL-1, our results indicate that DAAO can adopt multiple orientations on the surface, which are ultimately responsible for significant differences in catalytic activity. that DAAO can adopt multiple orientations on the surface, which are ultimately responsible for significant differences in catalytic activity. D-amino acid oxidase (DAAO) with single-walled carbon nanotubes (CNT) by spectroscopic ellipsometry. Dynamic adsorption experiments were performed at different experimental conditions. In addition, the activity of the enzyme adsorbed at different conditions was studied. Our results indicate that DAAO can be adsorbed to CNT at different pH values and concentrations by a combination of hydrophobic and electrostatic interactions. Considering that the highest enzymatic activity was obtained by adsorbing the protein at pH 5.7 and 0.1 mg·mL-1, our results indicate that DAAO can adopt multiple orientations on the surface, which are ultimately responsible for significant differences in catalytic activity. that DAAO can adopt multiple orientations on the surface, which are ultimately responsible for significant differences in catalytic activity. ·mL-1, our results indicate that DAAO can adopt multiple orientations on the surface, which are ultimately responsible for significant differences in catalytic activity.